Nouveaux témoignages du culte de Cubèle phrygienne en Sicile - Pedrucci, Giulia (Tekmeria, 2017)
The aim of the present article is to present some new evidence of the possibility of a cult dedicated to Cybele in Sicily, which could suggest the existence of contacts between the Near East and Sicily before the Greek colonization.